Utilization of Pleurotus Sajor-Caju stalks as feed supplement in diet of juvenile Oreochromis niloticus (tilapia) / Thenamutha Muniandy - Muniandy, Thenamutha (2010)
In this study, the potential use of the powdered Pleurotus sajor caju (Oyster mushroom) stalks as a supplemented feed for juvenile Oreochromis niloticus was evaluated by observing the growth level(length, body weight and specific growth rate (SGR), survival and also by measuring the water quality parameters (pH, temperature, Ammonia, Nitrite, Nitrate and dissolved oxygen). Stalks of P. sajor-caju are a waste product from the mushroom industry which is known to be an economical, abundant and good protein source. Diets were incorporated with commercial feed in proportion of P. sajor-caju25% (Diet1), P. sajor-caju50% (Diet2) and control feed(Diet3). The survival of O. niloticus on the final week, for the fishes that were fed with Diet1 showed highervalue of 85.18±0.85% compared to Diet3 with 79.63±0.64%. Meanwhile the growth performance(body length and weight) of the tilapia fed with Diet1 (4.40 ± 0.03cm; 9.66 ± 0.48g) was higheroncomparedtoDiet2 (4.26 ± 0.04cm; 9.42 ± 0.27g) and Diet3 (4.21 ± 0.01cm; 9.16 ± 0.18g). Moreover, Diet1 isalsohigher inSGR (1.65 ± 0.01%) compared to other diets with a significant level of P<0.05. P. sajor-caju supplemented diets(Diet1 andDiet2) were rich in protein and the moisture value is also high when compared to the control(Diet3). On the other hand the contents of fat, carbohydrate and ash were higher than supplemented diet. Crude fiber was higher in Diet1 andDiet3 but low amount in Diet2. Water quality between groups of diet and with in groups of triplicatetanks were almost similar for all the parameter studied except for the ammonia concentration. In thisstudy, ammonia concentration was higher in tank fed with Diet1 (5.95 ± 0.19mg/L)and Diet 2 (5.14 ± 0.17mg/L) supplemented diet compared to the Diet 3 (2.18 ± 0.07mg/L). However this higher ammonia concentration does not affect the growth and survival of tilapia. Meanwhile, least nitrite concentration was found in the Diet3 and Diet1 with0.02 ± 0.002mg/L and0.22 ± 0.003mg/L respectively compared to Diet2 sample with 0.03 ± 0.00mg/L. The nitrate concentration over eight weeks of feeding trial showed no significant value for all three diets. Besides that, the pH was maintained in therangeof7.26 ± 0.01 to7.34 ± 0.08, whereitwasslightlyalkalineandclosertoneu- tral. The temperature for all tanks with the three diets showed significant difference between Diet2 and Diet3 as comparedto Diet1. The DO levels were 5.81 ± 0.13ppm, 5.70 ± 0.63ppmand5.24 ± 0.15ppm for water tank fed with Diet1, Diet2 and Diet3 respectively. Eventhough, tilapias consuming Diet1 showed slightly higher DO concentration compared to otherdiets, yet there was a no significant difference(P>0.05) inDO measurement.